2005
DOI: 10.1093/jn/135.11.2566
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid Predominates in the Membrane Phosphoglycerides of the Early and Term Human Placenta

Abstract: The aim of this study was to determine whether the high concentration of arachidonic acid (AA) in term placentae accumulates during pregnancy or is an inherent characteristic of placental lipids. We investigated the lipid content and fatty acid composition of the human placental phospholipids at 2 gestational periods, early in pregnancy (8-14 wk, n = 48) and at term (38-41 wk of gestation, n = 19). The subjects were healthy, normotensive, and free of medical and obstetric complications. The lipid concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 38 publications
1
21
1
Order By: Relevance
“…In addition, there was no difference in either of the two FA between the Asian, African, and Caucasian subjects in the control group. This is consistent with our previous study (31), which showed that ethnicity had no significant effect on placental AA and DHA.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, there was no difference in either of the two FA between the Asian, African, and Caucasian subjects in the control group. This is consistent with our previous study (31), which showed that ethnicity had no significant effect on placental AA and DHA.…”
Section: Discussionsupporting
confidence: 94%
“…First, the human placenta is a vascular organ rich in phospholipids (28)(29)(30), which in turn are rich in PUFA, particularly AA (31). Second, the placenta lacks desaturase activity (13), and is thought to be primarily dependent on maternal circulation for the supply of these vital FA.…”
Section: Discussionmentioning
confidence: 99%
“…Also, LA and DGLA (n-6 PUFA) are found in higher levels compared to placental LC n-3 PUFA (ref. 72,74,75 ). In relation to this, AA-derived PG are related to the maintenance of pregnancy and initiation of labor 76 .…”
Section: A Fatty Acids During Gestation: Maternal and Placental Metamentioning
confidence: 99%
“…Placental unsaturated phospholipids are dominated by AA, which appear at a several-fold greater concentration than DHA and other PUFA. AA precursors linoleic acid (LA) and di homo-␥-linolenic acid (DGLA) are also at higher concentrations than n-3 precursors [Bitsanis et al, 2005]. Biosynthesis of AA from its primary dietary precursor LA is thought to be rapid because the 3 enzymatic steps ( ⌬ 6-desaturation, elongation, ⌬ 5-desaturation) are usually considered to be rapid compared to the 7 steps involving 2 organelles in the accepted pathway for DHA biosynthesis.…”
Section: Conceptus (Placenta and Fetal) Pufamentioning
confidence: 99%